Inside the Coliseum 21 (C.P. Johnston Co.)
Inside the futuristic Coliseum 21 at Century 21 Exposition, America's Space Age World's Fair. Shown is the fascinating two-level home of the year 2000 A.D. and part of the imaginative suburban recreation section. Unfolded in this 4-acre theme building are eye-popping predictions of life in the coming century.